2016
DOI: 10.1016/j.ymeth.2016.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the molecular dynamics flexible fitting method for cryo-EM modeling

Abstract: Molecular Dynamics Flexible Fitting (MDFF) is an established technique for fitting all-atom structures of molecules into corresponding cryo-electron microscopy (cryo-EM) densities. The practical application of MDFF is simple but requires a user to be aware of and take measures against a variety of possible challenges presented by each individual case. Some of these challenges arise from the complexity of a molecular structure or the limited quality of available structural models and densities to be interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(106 citation statements)
references
References 101 publications
(134 reference statements)
0
106
0
Order By: Relevance
“…Coot (Emsley and Cowtan, 2004) was used for model building. Initial rounds of refinement used xMDFF, with input files prepared in VMD (Humphrey et al, 1996) using the MDFF-GUI (McGreevy et al, 2016) with default molecular dynamics parameters (McGreevy et al, 2014), improving R work /R free from 0.50/0.54 to 0.41/0.45. The model was further refined using PHENIX with additional local refinements using xMDFF.…”
Section: Methodsmentioning
confidence: 99%
“…Coot (Emsley and Cowtan, 2004) was used for model building. Initial rounds of refinement used xMDFF, with input files prepared in VMD (Humphrey et al, 1996) using the MDFF-GUI (McGreevy et al, 2016) with default molecular dynamics parameters (McGreevy et al, 2014), improving R work /R free from 0.50/0.54 to 0.41/0.45. The model was further refined using PHENIX with additional local refinements using xMDFF.…”
Section: Methodsmentioning
confidence: 99%
“…Each equilibrated structure was then refined via a density-guided MD simulation step (MDFF1) 69, 71 . The last frame of this trajectory was used as the input model for Rosetta density-guided local building and refinement (Rosettal) 58 .…”
Section: Methodsmentioning
confidence: 99%
“…As opposed to Rosetta, MD simulations use a purely physics-based approach, based on integrating the equations of motion in molecular mechanics force fields 70 . The molecular dynamics flexible fitting method (MDFF) uses MD simulations to refine protein structure guided by experimental cryo-EM density maps 69, 71 . MDFF has been successfully applied to various biological systems, including membrane proteins 7173 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More concretely, for 49 EM maps of a wide range of resolutions, we ran two structure fitting/refinement protocols, Molecular Dynamics Flexible Fitting (MDFF) (McGreevy et al, 2014; McGreevy et al, 2016) and Rosetta (Wang et al, 2015) starting from the deposited structure models and observed changes of cross correlation of the models to the EM maps and the energy of those structures. These two programs were chosen because they are among the most popular structure modeling and refinement tools used for protein structure determination of EM maps.…”
Section: Introductionmentioning
confidence: 99%